Anxiety No More: The EFL Students Voice On the Use FTF VS SCMC toward Their Speaking Anxiety - Safira Yasinta Karenina Hidayat; Djatmika Djatmika; Ngadiso Ngadiso (VELES Voices of English Language Education Society, 2022)
In this era, many researchers already conduct research on using CMC in the education field. Several researchers have explored using SCMC (audio and text) and ACMC to know the benefits for students' skills in a foreign language. However, this study explores using SCMC (audio and video) to know the students' perception of their speaking anxiety. The present qualitative study examines the students' voices using FTF or SCMC toward their speaking anxiety. This study aims to know the students' voices related to their speaking anxiety in English under two conditions: Face to face and Synchronous computer-mediated communication. These voices were presented by five students of English language education who were interviewed about using FTF and SCMC. The result shows that the participants prefer to use SCMC to reduce anxiety while they speak English. An analysis of data from the interview explicates that two themes were related to EFL students' speaking anxiety, including (1) fear of making mistakes and (2) feeling under pressure. The interview results also stated the advantages and disadvantages of both environments (FTF and SCMC). This study implies that SCMC can increase students' confidence in speaking English. Therefore, this paper suggests that teachers should provide a supportive environment and support their students in practicing speaking in English using SCMC.